Forecasting Demand Produk Batik Di Tengah Pandemi Covid-19 Studi Pada Usaha Batik Fendy, Klaten - Pasca Riani, Lilia; Afandi, Muhammad Roestam (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2020)
The objectives of this study are forecast the demand for batik cloth and batik clothing in May 2020 and analyze the accuracy of forecasting demand for batik cloth and batik clothing. This research is a descriptive study with a quantitative approach. Using data by interviews with Batik Fendy Business Managers and actual sales data from November 2019 to April 2020. There are two stages of data analysis that is calculating demand forecasting of batik cloth and batik clothing for May 2020 with the Linear Exponential Smoothing method uses a combination of α 0,8 / β 0,1 and α 0,9 / β 0,2 constant. While the second stage is to analyze the accuracy of the method of demand forecasting using the MAPE Technique. The results of this study are for batik cloth products, predicted sales demand for May 2020 is 316 pieces with 30% MAPE. As for the batik clothing forecasting demand for May 2020 is 432 pieces with a MAPE of 19,8%.